The Implications of Changes in the State Budget (APBN) through Presidential Instruction (Inpres) from the Perspective of Administrative Law - Kusuma, Lalu Aria Nata; Syarif, Nawaz (Faculty of Law, University of Dr. Soetomo, 2025)
In realizing the prosperity and well-being of the people, the State Revenue and Expenditure Budget/State Budget (APBN) plays a crucial role in reflecting the government's economic policy. According to the provisions in the State Financial Law, changes to the APBN during the fiscal year can only be made through the instrument of the Revised APBN Law. However, Presidential Instruction Number 1 of 2025, which was issued, alters the established APBN. This change raises questions about whether the presidential instruction, as a discretionary power, can be used to modify the APBN and what the implications are. The research method used is normative legal research utilizing a legislative and conceptual approach. The research results indicate that presidential instructions are regulations used to interpret vague and stagnant rules to address existing issues. However, this does not mean that presidential instructions can be used freely. In the context of changing the posture of the APBN through presidential instructions, this research shows that such actions do not meet the objectives and requirements for issuing discretion as stipulated in the Government Administration Law. The failure to meet these conditions has implications, namely: 1) the presence of Presidential Instruction No. 1/2025 is a form of abuse of power by state administrative officials; 2) the normalization of abusive discretionary practices by the government; and 3) it shows the failure of the House of Representatives (DPR) to perform its function properly. Therefore, it is important for the government, as administrative officials who can issue discretion, to adhere to existing guidelines when issuing policy regulations.